KARAKTERISTIK BIO-OIL HASIL PIROLISIS AMPAS TEBU - Emi Erawati; Wahyudi Budi Sediawan; Panut Mulyono (Jurnal Kimia Terapan Indonesia, 2013)
Bagasse (Saccarum oficinarum L) is a waste of sugar mills that can be utilized for a variety of chemicals. The purposes of this study are to determine the percentage of compounds and physical properties of bio-oil, to determine the effect of variations of particle size and heating rate on the yields of bio-oil. Pyrolysis has been carried out in a reactor made of steel pipe type 5737 with dimension: diameter 7.62 em and a length of 3 7 cm.. The reactor was inserted into the furnace with a diameter of 15.24 em and a length of 40 em. One hundred and fifty grams of bagasse (Saccarum oficinarum L) has been inserted into the reactor without the presence of oxygen at atmospheric pressure. Pyrolysis has been carried out at the particle size of (-20+25) mesh, (-25+30) mesh, (-30+35) mesh, (- 35+40) mesh, and -40 mesh with electrical voltage of 100, 105, 115, and 120 volt. Produced of bio-oil has the following properties: brown color, pH of 2.96 to 3.03, viscosity of 1.3306 to 1.5101 cp, and density of 1.03 to 1.5 g/mL. The largest content of the compound is acetic acid (59, 72%). The highest yields percentage of the particle size is (40,32%) on (-20+25 mesh) with the highest yields percentage of electrical voltage is 38,82% on 105 volt.Keywords : Bagasse, acetic acid, bio-oil, pyrolysis, yields